Model-free wind farm control based on random search - Mohd Ashraf, Ahmad; Hao, Mok Ren; Raja Mohd Taufika, Raja Ismail; Ahmad Nor Kasruddin, Nasir (IEEE, 2017)
This paper explores a model-free approach based on the random search (RS) algorithm for maximizing wind farms power production. The RS based approach is utilized to find the optimal control parameter of each turbine in maximizing the wind farm total power production. The Horns Rev wind farm model with turbulence interaction between turbines is used to validate the proposed approach. Simulation results demonstrate that the random search approach produces higher total power production as compared to the existing method.